PAROKI RAMAH ANAK SEBAGAI WUJUD DIAKONIA GEREJA TERHADAP PERSOALAN HUMAN TRAFFICKING - Seran, Florensia Imelda; Denar, Benediktus; Jewadut, Jean Loustar (Bahasa Indonesia, 2024)
The Catholic Church pays full attention to efforts to eradicate human trafficking that affects children Catholic Church pays full attention to efforts to eradicate human trafficking that affects children and women. The Church realizes that human trafficking is a humanitarian issue that must be handled seriously. Humans, including children and women, are the image of God and have the same dignity as all people. This concern is a form of Church diakonia, namely serving and protecting the small and weak. One of the Church's efforts is realized through a child-friendly parish program. A child-friendly parish is a pastoral program that prioritizes children to grow integrally as members of the Church. The approach used to obtain information about child-friendly parish programs is qualitative, using interview and observation methods. From this research it is concluded that the child-friendly parish program as a form of Church diakonia has not been fully understood and realized in parish life. So at the end of this article the author states several responsibilities of the Church as a form of Church diakonia in relation to human trafficking cases and offers several practical efforts that can be made by the Church to improve the quality of Church services to children through child-friendly parish programs.